The Perfect Game: An Ecological Systems Approach to the Influences of Elite Youth and High School Baseball Socialization - Max Klein; Charles Macaulay; Joseph Cooper (Bowling Green State University, 2020)
The purpose of this study was to examine the elite youth and high school baseball socialization process as a whole and the role of professionalization and corporatization in this process. The unique nature of baseball's development model in the United States (U.S.), through a dual-track feeder system (college or minor leagues) allows for a wide-range of challenges and sociological factors to influence elite youth and high school prospects. Understanding players' experiences exposes these challenges and sociological factors. Semi-structured interviews were conducted with four former elite youth and high school baseball players, one parent of a player, two coaches, and two media members. Using Bronfenbrenner's (1977) ecological systems theory, the authors examined multi-level sociological factors contributing to participants' socialization experiences. Key findings revealed corporate-level factors including National Collegiate Athletic Association (NCAA) bylaws, Major League Baseball's (MLB) collective bargaining agreement (CBA), and related commercialized changes in elite youth and high school baseball had a pronounced influence on baseball players' socialization processes. Implications for policy and practice are discussed.